2015
DOI: 10.1002/nau.22943
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with mirabegron therapy for overactive bladder: A real life experience

Abstract: Persistence rates with mirabegron in this group of patients for OAB are satisfactory. The commonest reasons for discontinuation are unmet treatment expectations and adverse effects. We had very few treatment-naïve patients and so further studies are required to assess mirabegron persistence rates with longer-term follow up, as first-line treatment and in different groups of OAB severity. Neurourol. Neurourol. Urodynam. 36:404-408, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Meta-analyses have shown similar efficacy to available anticholinergic drugs, but with a much reduced incidence of dry mouth 138,139 , and lower efficacy than intravesical onabotulinumtoxinA 140 . Mirabegron has the potential to exacerbate hypertension 131 , but is otherwise well tolerated compared with most anticholinergics, with good persistence 141 . However, for most patients, symptom improvement is quite modest.…”
Section: Managementmentioning
confidence: 99%
“…Meta-analyses have shown similar efficacy to available anticholinergic drugs, but with a much reduced incidence of dry mouth 138,139 , and lower efficacy than intravesical onabotulinumtoxinA 140 . Mirabegron has the potential to exacerbate hypertension 131 , but is otherwise well tolerated compared with most anticholinergics, with good persistence 141 . However, for most patients, symptom improvement is quite modest.…”
Section: Managementmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72). [13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72).…”
Section: Discussionmentioning
confidence: 99%
“…Metaanalyses have shown similar efficacy to available anticholinergic drugs, but with a much reduced incidence of dry mouth 138,139 , and lower efficacy than intravesical onabotulinumtoxinA 140 . Mirabegron has the potential to exacerbate hypertension 131 , but is otherwise well tolerated compared with most anticholinergics, with good persistence 141 . However, for most patients, symptom improvement is quite modest.…”
Section: Medical Interventionsmentioning
confidence: 99%